The Influence of Marketing Mix on Purchase Decision in the Kiyoptiykey Entrusted Service - Novianti Amalia Setiawati; Nandang Nandang; Nizza Nadya Rachmani (The Future of Education Journal, 2025)
Amidst the growing interest of Indonesians in Korean culture, especially K-Pop, the demand for K-Pop merchandise has increased. However, direct purchases from official platforms based overseas are often hampered by high shipping costs and taxes, causing many consumers to turn to entrusted service. Kiyoptiykey is one such proxy service for purchasing K-Pop merchandise. Despite high market interest, Kiyoptiykey has experienced a decline in sales because the majority of transactions come from repeat customers, while the number of new customers has not increased significantly. Therefore, this study was conducted to analyze the effect of the marketing mix on purchasing decisions for Kiyoptiykey's entrusted service using descriptive quantitative methods on 118 respondents who were consumers who had used the service or purchased merchandise from Kiyoptiykey at least once. Data analysis was performed through validity and reliability tests, classical assumption tests, and hypothesis testing using simple linear regression with the help of SPSS. The results of this study indicate that all dimensions of the marketing mix have a positive effect on purchasing decisions and influence 80% of them. These findings identify that the more effective the marketing mix strategy, the stronger the consumer's purchasing decision for Kiyoptiykey's entrusted service.